Democratising Ukraine by Promoting Decentralisation? A Study of Swiss-Ukraine Cooperation - Oksana Myshlovska (Revue Internationale de Politique de Développement)
This working paper focuses on cooperation between Switzerland and Ukraine to support decentralisation, local government reforms, and a decentralised provision of services at the local level. Decentralisation has become a central priority for the Ukrainian government, which came to power after the fall of the Yanukovych regime in 2014, and is seen as a way not only of democratising the country but most importantly as a way of dealing with the conflict that started in eastern Ukraine the same year. The paper studies the political factors that have blocked the process of reform with a particular focus on the role of the two most eastern oblasts, the centre of the conflict, and the implementation of a decentralised service delivery model by Switzerland in several pilot communities in Ukraine. The paper suggests that Switzerland could pay more attention to the political factors that have obstructed decentralisation and local government reform, leverage better ‘the drivers of change’, and better address regional factors in order to more effectively promote the reform process at the national level.  The paper finds that the model of a decentralised service delivery developed and implemented by Switzerland, involving greater civic participation from local communities and the improvement in the capacities of local governments, has been successful, and has a wider democratisation potential. The model’s impact, however, has been limited as it was implemented only in several pilot communities, and Switzerland has not yet developed an approach to successfully scale up the model across the country and apply it to solving a wider number of social, political and economic issues. The findings of the paper are especially pertinent in view of the recent Swiss commitment to becoming more ‘political’ in development cooperation and to focusing more on the political side of democracy promotion.